Material knowledge in collaborative designing and making - A case of wearable sea creatures - Härkki, Tellervo; Seitamaa-Hakkarainen, Pirita; Hakkarainen, Kai (FormAkademisk, 2016)
This article is based on a study of novice designers’ knowledge of materials in a challenging collaborative assignment. We approached material knowledge from two complementary viewpoints: the dimensions of knowledge shared during designing, and how student teams built new knowledge during making. We found that both modalities studied—namely, words and gestures—contributed to advancement in designing. The modalities became specialised: While words served mainly to identify materials and to describe visual qualities, gestures conveyed information about size, shape, location and dynamic dimensions, such as movement and change over time, as well as signature qualities based on embodied experience. During making, ambitious teams took material decisions and the challenge of authenticity seriously, but the tight timeframe and budget compelled them to favour pragmatic choices.